Airway epithelial phosphoinositide 3-kinase-δ contributes to the modulation of fungi-induced innate immune response. Issue 8 (5th April 2018) - Jeong, Jae Seok; Lee, Kyung Bae; Kim, So Ri; Kim, Dong Im; Park, Hae Jin; Lee, Hern-Ku; Kim, Hyung Jin; Cho, Seong Ho; Kolliputi, Narasaiah; Kim, Soon Ha; Lee, Yong Chul
Abstract : Background: Respiratory fungal exposure is known to be associated with severe allergic lung inflammation. Airway epithelium is an essential controller of allergic inflammation. An innate immune recognition receptor, nucleotide-binding domain, leucine-rich-containing family, pyrin-domain-containing-3 (NLRP3) inflammasome, and phosphoinositide 3 kinase (PI3K)-δ in airway epithelium are involved in various inflammatory processes. Objectives: We investigated the role of NLRP3 inflammasome in fungi-induced allergic lung inflammation and examined the regulatory mechanism of NLRP3 inflammasome, focusing on PI3K-δ in airway epithelium. Methods: We used two in vivo models induced by exposure to Aspergillus fumigatus ( Af ) and Alternaria alternata ( Aa ), as well as an Af -exposed in vitro system. We also checked NLRP3 expression in lung tissues from patients with allergic bronchopulmonary aspergillosis (ABPA). Results: Assembly/activation of NLRP3 inflammasome was increased in the lung of Af -exposed mice. Elevation of NLRP3 inflammasome assembly/activation was observed in Af -stimulated murine and human epithelial cells. Similarly, pulmonary expression of NLRP3 in patients with ABPA was increased. Importantly, neutralisation of NLRP3 inflammasome derived IL-1β alleviated pathophysiological features of Af -induced allergic inflammation. Furthermore, PI3K-δ blockade improved Af -induced allergic inflammation through modulation of NLRP3 inflammasome, especially in epithelial cells. This modulatory role of PI3K-δ was mediated through the regulation of mitochondrial reactive oxygen species (mtROS) generation. NLRP3 inflammasome was also implicated in Aa -induced eosinophilic allergic inflammation, which was improved by PI3K-δ blockade. Conclusion: These findings demonstrate that fungi-induced assembly/activation of NLRP3 inflammasome in airway epithelium may be modulated by PI3K-δ, which is mediated partly through the regulation of mtROS generation. Inhibition of PI3K-δ may have potential for treating fungi-induced severe allergic lung inflammation.